Slippage of Gastric Banding for Mobid Obesity: case report and review of literature: Slippage of Gastric Banding - Coco, Danilo; Leanza, Silvana (British Journal Of Surgical Science, 2021)
Background: laparoscopic adjustable gastric banding (LABG) remains the commonest and less invasive bariatric operation. It has many advantages in the treatment of obesity and is associated with low morbidity and mortality rates.When it happens a Gastric Band Slippage (GBS), part of the gastric fundus herniates through the band. Removal of GB is necessary to prevent necrosis of the herniated stomach. Case report: We present a case of a 40-year-old female patient who was admitted for a huge gastric pouch dilatation after 3 years of underwent LAGB. Conclusion: The LAGB is one of the most common procedures used for the treatment of morbid obesity. The complications are generally not mortal but it is necessary that complications have been recognized by general surgeon and physicians should be aware of the symptoms. Diagnosis of GBS can be made with signs or symptoms and patient’s medical history, with the use of oral contrast X-ray studies or CT Scan and surgical intervention is necessary.